Climatic changes and caribou abundance in northern Québec over the last century - Crête, Michel; Payette, Serge (Rangifer, 1990)
The temperature increase observed in the Northern hemisphere during the first half of this century was also detectable in Québec; it affected both summer and winter. In northern Québec, warmer summers stimulated growth and favored range expansion of trees and shurbs. Based on black spruce krummholz height and water level in lakes, the warmer period was also characterized by greater snowfall and deeper snow cover. This period of deep snow coincided with apparent caribou scarcity. Three hypotheses were explored to relate increased temperature with caribou decline: 1) destruction of winter habitat due to high frequency of forest fires, 2) increased energy cost to obtain forage in deep snow and 3) delayed melting of snow on calving grounds that shortened the time to raise calves. The combined effect of the 3 mechanism could explain caribou scarcity, particularly for the Rivière George herd whose calving ground becomes snow free in late June. Ways to test the third hypothesis are proposed.